2016
DOI: 10.1210/en.2015-1959
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal Hormones Rapidly Enhance Spatial Memory and Increase Hippocampal Spine Density in Male Rats

Abstract: 17β-estradiol (E2) rapidly, within minutes, activates behaviors and cognition by binding to membrane estrogen receptors, activating cell signaling cascades and increasing dendritic spines. In female rodents, E2 enhances spatial memory within 2-4 hours, and spine density is increased in the CA1 area of the hippocampus within 30-60 minutes. Although chronic gonadal hormone treatments in male rats alter cognition and spines/spine synapses and acute hormone effects occur in hippocampal slices, effects of acute, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 49 publications
7
74
0
Order By: Relevance
“…In particular, dendritic spines, the site of most excitatory synapses, respond very rapidly to estrogen treatment. In the hippocampus, 17β-estradiol administration results in a transient increase in density and length (Jacome et al, 2016; MacLusky et al, 2005; Mukai et al, 2007; Murakami et al, 2006; Mendez et al, 2011; Srivastava, et al, 2008; Tuscher et al, 2016). In behaviorally naïve ovariectomized female mice, it was also found that systemic treatment with 17β-estradiol (Phan et al, 2012), ERα agonist PPT (Phan et al, 2011) and GPER agonist G1 (Gabor, Lymer et al, 2015) rapidly increased dendritic spine density in CA1 field of the hippocampus, while ERβ agonist DPN decreased it (Phan et al, 2011).…”
Section: Rapid Action Of Estrogens and Their Receptors: Implicatiomentioning
confidence: 99%
“…In particular, dendritic spines, the site of most excitatory synapses, respond very rapidly to estrogen treatment. In the hippocampus, 17β-estradiol administration results in a transient increase in density and length (Jacome et al, 2016; MacLusky et al, 2005; Mukai et al, 2007; Murakami et al, 2006; Mendez et al, 2011; Srivastava, et al, 2008; Tuscher et al, 2016). In behaviorally naïve ovariectomized female mice, it was also found that systemic treatment with 17β-estradiol (Phan et al, 2012), ERα agonist PPT (Phan et al, 2011) and GPER agonist G1 (Gabor, Lymer et al, 2015) rapidly increased dendritic spine density in CA1 field of the hippocampus, while ERβ agonist DPN decreased it (Phan et al, 2011).…”
Section: Rapid Action Of Estrogens and Their Receptors: Implicatiomentioning
confidence: 99%
“…Although rapid spine modulation via in vivo androgen treatment has not been studied extensively, the rapid increase in CA1 spines was observed 0.5‐2 hours after s.c. injection of testosterone (750 μg kg ‐1 ) in castrated male rats …”
Section: Analysis Of Spine Density and Spine Head Morphology: Mainly mentioning
confidence: 99%
“…Numerous investigations have been performed regarding the rapid E 2 effects on spines, in addition to isolated slices. In vivo E 2 treatment via s.c. injection rapidly increased (within 15‐40 minutes) the spine density in CA1 hippocampal neurones of ovariectomised (OVX) mice . The injection of E 2 rapidly (~30 minutes) increased the spine‐synapse density as a result of synaptic rearrangements in OVX female rats .…”
Section: Analysis Of Spine Density and Spine Head Morphology: Mainly mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the intuitive reasoning is that reducing Aβ levels should protect synapses, ameliorate neuronal plasticity and translate into beneficial effects on memory function. Thus, interventions that ameliorate spine density and plasticity also boost memory function (170)(171)(172). Conversely, manipulations that reduce neuronal connectivity and spine density subsequently alter memory (173,174).…”
Section: Potential Mediators Of Xbp1 Signaling In Neuronsmentioning
confidence: 99%